(untitled) (Revista Lusófona de Educação, 2024)
In the field of education, although not always in congruent senses or directions, assessment is particularly sensitive to political-ideological, pedagogical and cultural changes. What is highlighted is, first of all, an assumption that can and should continue to be empirically tested, especially in historical moments marked by profound changes. With some unpublished data and documents, or which have not had great visibility in research until now, what is precisely intended in this article is, in an exploratory way, to seek to understand whether or how the profound changes that have begun in Portuguese society have had an impact on pedagogical assessment, in a unique historical situation such as the Carnation Revolution of April 1974. This text revisits the students’ assessment (or pedagogical assessment) at two specific moments: the transition from the authoritarian Estado Novo to democracy, and the revolutionary period up to the 1st Constitutional Government. Privileging a sociological perspective, the text leaves open many questions that could give rise to future in-depth studies, in this or other disciplinary fields, or that could even constitute an object of study for a greater theoretical-conceptual and empirical investment. Keywords: student assessment; authoritarian regime; revolutionary period.